Chinese App User’s Needs Profile: From Questionnaire Measurement to Behavior Analysis - Sun, Zaoyi; Xu, Liang; Zhong, Qi; Qian, Xiuying (Frontiers in Psychology, 2021)
With the widespread use of mobile devices, the apps people install and use could be closely linked to their needs. A precise profile of user’s needs has become a vital foundation of user’s experience. Previous studies mainly rely on self-report to understand App user’s subjective attitudes towards a single App. Our research combined questionnaire measurement and behavior analysis to profile App user’s needs from a broader perspective. Based on the theoretical model of previous researches, study 1 developed a novel Chinese App user’s needs questionnaire measurement, which showed good reliability and validity. In study 2, authorized App usage data was collected to construct Chinese user’s behavioral needs profile. The results showed that Chinese user’s primary needs remained a relatively high consistency between questionnaire and the behavior data. The questionnaire-based and behavioral data-based needs profiles provide a reference for further personalized user experience design.